Patterns of nonadherence to antiepileptic drug therapy in children with newly diagnosed epilepsy - Modi, Avani C; Rausch, Joseph R; Glauser, Tracy A (JAMA : the journal of the American Medical Association, 2011)
Because of epilepsy's common occurrence, the narrow therapeutic and safety margins of antiepileptic medications, and the recognized complications of medication nonadherence in adults with epilepsy, identifying the rates, patterns, and predictors of nonadherence in children with epilepsy is imperative. The onset and evolution of antiepileptic drug nonadherence in children with newly diagnosed epilepsy remains unknown. To identify and characterize trajectories of adherence in children with newly diagnosed epilepsy over the first 6 months of therapy and to determine sociodemographic and epilepsy-specific predictors of adherence trajectories. Prospective, longitudinal observational study of antiepileptic drug adherence in a consecutive cohort of 124 children (2-12 years old) with newly diagnosed epilepsy at Cincinnati Children's Hospital Medical Center. Patients were recruited from April 2006 through March 2009, and final data collection occurred in September 2009. Objective adherence measured using electronic monitors. Fifty-eight percent of children with newly diagnosed epilepsy demonstrated persistent nonadherence during the first 6 months of therapy. Group-based trajectory models identified 5 differential adherence patterns (Bayesian information criterion = -23611.8): severe early nonadherence (13%; 95% confidence interval [CI], 8%-20%), severe delayed nonadherence (7%; 95% CI, 3%-12%), moderate nonadherence (13%; 95% CI, 8%-20%), mild nonadherence (26%; 95% CI, 19%-34%), and near-perfect adherence (42%; 95% CI, 33%-50%). The adherence pattern of most patients was established by the first month of therapy. Socioeconomic status was the sole predictor of adherence trajectory group status (χ(4)(2) = 19.3 [n = 115]; P < .001; partial r(2) = 0.25), with lower socioeconomic status associated with higher nonadherence. Five trajectory patterns were identified that captured the spectrum of nonadherence to antiepileptic drugs among children with newly diagnosed epilepsy; the patterns were significantly associated with socioeconomic status.